Las habilidades lingüísticas y el autoestima en niños de Inicial 2 de la Unidad Educativa ‘’Liceo Policial’’ de la ciudad de Riobamba. - Ñauñay Salguero, Sofia Belen (2024)
The general objective of this research work entitled Language skills in the self-esteem of children in Kindergarten II of the Educational Unit ‘’Liceo Policial’’in the city of Riobamba, is to determine the importance of language skills in the development of self-esteem of children in Kindergarten 2 in the educational institution.To achieve this objective, a qualitatively oriented methodology was employed, making use of a non-experimental design and an approach base don existing literatura. In this way, it was configured as a field study, allowing reliable data to be obtained from the real environment of the institution through the observation technique. This technique focusedon how language skills contribute significantly to the formation of a positive self-image.An observation sheet was developed with specific indicators to evaluate the behavior and development of the students in relation to the topic of study. The sample of this study consisted of a total of 19 children, 10 boys and 9 girls aged between 4 and 5 years. After making the required observation, it was noted that most of the children do not exhibit adequate progressin theirlanguage skills. At the end of the análisis of the observed results, various recreational activities have been implemented to stimulate the growth of oral and written language in children,which favors their cognitive and social evolution.